The Impact of Entrepreneurial Orientation on Performance Company: The Moderating Effect of the External Environment: Tunisian case - Zouari, Soufien (Rescollacom (Research Collaborations Community), 2024)
Although entrepreneurial orientation (EO) has been shown to play a key role in increasing firm performance (FP), the effects of EO have been extremely over simplified. The plethora of empirical studies on EO and FP suggest that the EO-FP relationship is linearly positive regardless of the amount of EO investment. The results show that EO increases FP at the bounded level. We argue that the excessive use of EO and organizational incapability may contribute to the non-linearity of such effects. We also find that highly dynamic environments enhance the EO-FP relationship. We present prescriptive implications to practitioners on the antecedent conditions for EO practices.